Management of leiomyoma of the transverse colon: case report - Abruzzo, Alida; Spinelli, Gabriele; Martorana, et al., Anna (European Journal of Oncology and Environmental Health, 2014)
Colonic leiomyoma is a mesenchymal tumor that arises from the muscularis mucosae or muscularis propria and is composed of well-differentiated smooth muscle cells with no atypia. It is often incidentally found since its growth affects the submucosal layer and the lesion is covered with normal epithelium. Endoscopic ultrasonography is recommended to define the grade of infiltration of the tumor and eventually lymph node involvement. Histological examination is critical to establish the nature of the tumor and its behaviour. In the case of a voluminous tumor surgical treatment is needed. We report the case of a patient that underwent colonoscopy showing the presence of a neoformation at 70 cm from ileocecal valve occupying half lumen of transverse colon. A surgical resection was performed and histological analysis confirmed the presence of a leiomyoma.